Seasonal Dynamics of Zygnema (Zygnematophyceae) Mats from the Austrian Alps - Trumhová, Kateřina; Klimešová, Vanda; Pichrtová, Martina (Microbial ecology, 2023)
Filamentous green algae of the genus Zygnema are an essential part of hydro-terrestrial ecosystems. Despite several studies on their resistance to natural stresses, little is known about the composition of their assemblages and the changes they undergo over time. Two sites at altitudes above 2200 m a.s.l. in the Austrian Alps were selected for a 2-year observation period and sampled five times. Molecular phylogenetic analysis of the 152 isolated strains of Zygnema sp. was performed based on the rbcL and trnG sequences. Seven genotypes were found at these sites during the samplings, but their proportion varied throughout the seasons. The site with a more stable water regime also had a more stable representation of genotypes, in contrast to the site with fluctuating water availability. The mats formed resistant pre-akinetes at the end of the season with reduced photosynthetic activity. Contrary to expectations, the mats were not exposed to extremely cold temperatures in winter due to snow cover. Some genotypes have been previously observed at this site, indicating that the population composition is stable. This work highlights the importance of resistant pre-akinetes in surviving winter conditions, the ability of algae to re-establish mats, and the need to address the hidden diversity of the genus Zygnema.
Keywords: Cryptic diversity; voda; Seasons; Phylogeny; Austria; ekosystém; Hidden diversity; Chlorophyll fluorescence; Streptophyta; Freezing; Overwintering; roční období; Rakousko; Ecosystem; Water; fylogeneze